Confronting Barriers to Cropping System Diversification - Mortensen, David A.; Smith, Richard G. (Frontiers in Sustainable Food Systems, 2020)
There is no shortage of data demonstrating that diversified cropping systems can sustain high levels of productivity with fewer external inputs and lower externalities compared to more simplified systems. Similarly, data exist indicating diverse cropping systems have greater capacity to buffer against and adapt to weather extremes associated with climate change. Yet, agriculture in the US Corn Belt and other major crop production regions around the world continues to move toward simplified rotations grown over increasingly large acreages. If our goal is to see more of the agricultural landscape made up of diverse agricultural systems and the ecosystem services they provide, it is critical we understand and creatively address the factors that both give rise to monocultures and reinforce their entrenchment at the exclusion of more diversified alternatives. Using the current state of farming and agriculture policy in the US as a case study, we argue that a pernicious feedback exists in which economic and policy forces incentivize low diversity cropping systems which then become entrenched due, in part, to a lack of research and policy aimed at enabling farming practices that support the diversification of cropping systems at larger spatial scales. We use the recent example of dicamba-resistant crops to illustrate the nature of this pernicious feedback and offer suggestions for creating “virtuous feedbacks” aimed at achieving a more diversified agriculture.